On The Performance of The Effects of Temperature Variation in Ultrafast Incoherent Fiber-Optic CDMA Systems With SOA-Based Tunable Dispersion Compensator - Che-Wei Chang; Guu-Chang Yang; Ivan Glesk; Wing C. Kwong (IEEE Photonics Journal, 2019)
Recent studies show that temperature variation in ultrafast incoherent fiber-optic code-division multiple-access (FO-CDMA) systems using picosecond multiwavelength codes is a realistic problem even though dispersion-compensating fiber is utilized. The phenomenon creates distortions in auto- and cross-correlation functions and then worsens system performance. A physical-layer mitigation approach has been reported by using a recently demonstrated semiconductor-optical-amplifier-based tunable dispersion compensator to fully recover the auto-correlation peaks. Applying the concept of “chip granularity” to account for the effects of temperature variation to the cross-correlation functions, this paper formulates a new performance-analytical model for such FO-CDMA systems. The model also supports adjustable quality-of-services through code weight control.